Peran Sektor Pertanian dalam Mewujudkan Ketahanan Pangan untuk Pemberdayaan Ekonomi di Pulau Sumatera - Maya Gita Safitri; Meliana Agustin; Ilham Syahroni; Erlin Kurniati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Sumatra Island has abundant natural resources, one of which is agricultural land. The agricultural sector plays an important role in the economic structure including the level of food security. Thus, the problem can be formulated in the form of how the role of the agricultural sector and food security is to the economic system on Sumatra Island. This research method is qualitative research with a literature review methods using literature collected in various sources. The purpose of this writing is to describe how the agricultural sector and food security play an important role in the economic system on Sumatra Island. The results of the study show that the agricultural sector plays an important role in supporting food security in the economic system in Sumatra even though it is faced with the challenges of climate change and land conversion. Therefore, collaboration between the community, private sector, and government is needed to improve technology and innovation in food crop diversification.